Climate-growth relationships and pointer year analysis of a Siberian larch (Larix sibirica Ledeb.) chronology from the Mongolian mountain forest steppe compared to white birch (Betula platyphylla Sukaczev) - Alexander Gradel (Forest Ecosystems, 2017)
Abstract Background Forest area, stand quality and growth of Siberian larch in Mongolia have decreased significantly over recent decades. This forest decline is frequently attributed to factors such as unregulated logging, increased ecological disturbances (primarily fire) and climate change. In this study, we analyzed climate-growth response and pointer years for Siberian larch observed in the Altansumber forest research area in the Mongolian mountain forest steppe zone. We compare our results with previously published results of white birch from the same area. Methods We built a reference chronology from wood core samples taken from 30 trees in three neighboring larch stands. Climate-growth relationships were analyzed monthly and seasonally over the period 1962–2009 using climate data from the Eroo weather station. Pointer year analysis covered the same time frame. Results Our analysis of the larch chronology showed that precipitation during autumn of the previous year and directly before the growing season of the current year was the most decisive factor determining tree-ring growth. Regional pointer year analysis further indicated that a humid summer and autumn followed by a warm spring support current-year tree-ring growth in these larch stands. Our findings were comparable to a white birch study in the same area. The larch trees, however, showed stronger growth performance and were more tolerant of higher temperatures, notably in spring during peak fire season. Conclusions Water availability is the decisive factor for larch growth in the mountain forest steppe zone. The chronologies showed no climatic indication of insect infestations. Differences in climate-growth relationships of birch and larch trees during peak fire season may to some degree be explained by their respective means of protecting themselves against low-intensity surface fires (e.g. thick bark of larch). These fire events occur regularly in the region and are influenced by climatic factors. Our analysis and comparison of climate tree-growth relationships may be valuable for developing climate- and disturbance-resilient forestry practices in Mongolian mountain forest ecosystems.